Keeping the faith: The university experience and apostasy - Grayson, J. Paul (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
In 1963, Glendon College, York University, located in Toronto Canada, admitted mainly Christian students of European origin to a small liberal arts program. Fifty years later the College remained small with a continuing, but less embracive, commitment to the liberal arts; however, the student body included large numbers of young adults who professed religions other than Christianity and came from backgrounds other than European. Within this context, this article focuses on the impact of the Glendon College experience on students’ religious identification and participation in religious services. Overall, I find that in the mid-sixties the College experience contributed to changes in the religious identification of students. By contrast, a half-century later, students’ post-secondary experiences were of little consequence for religiosity. One possible explanation for differences in the College effect is that because of the current racial and religious diversity of Toronto, students are more likely than in the past to confront their religious identities in high school.